Exploring the clinical complexity of cardio-facio-cutaneous syndrome: insights from a pediatric case series - Ou, Yuexu; Cao, Jie; Duan, Yuanhui; Chen, FengHua; Zhou, Jiwei; Li, Jieling; Gan, Xiaoming (Frontiers in Pediatrics, 2024)
Background: Cardio-Facio-Cutaneous syndrome (CFCS) is a rare autosomal dominant genetic disorder primarily caused by BRAF gene mutations, posing diagnostic challenges due to its multifaceted clinical presentation.Objective: To elucidate the clinical characteristics of pediatric CFCS patients, expanding the phenotypic spectrum to enhance early diagnostic capabilities, while also presenting the relationship between genotye and corresponding phenotype severity. Methods: From January 2015 to March 2022, four children diagnosed with CFCS in Children's Hospital of Chongqing Medical University were included for analysis. Whole exome sequencing (WES) was conducted to identify the types and locations of possible gene mutations. Neurological development was assessed using electroencephalography (EEG), magnetic resonance imaging (MRI) and Gesell developmental evaluation. Results: All four CFCS patients exhibited de novo BRAF gene mutations, manifesting with cardiac malformations, distinctive facial features, skin and hair changes, and neurological abnormalities. WES revealed that the specific BRAF mutations were closely linked to their clinical severity. Three patients displayed milder symptoms (case 1-3, genotype I or II), demonstrating stability or slight improvement, whereas one patient (case 4, genotype III) suffered from a severe phenotype characterized by profound neurological and digestive system impairments, leading to a significantly reduced quality of life and a grim prognosis. Conclusion: In CFCS patients, severe developmental delay and seizures are predominant neurological features, possibly accompanied by continuous spike-and-wave during sleep (CSWS) and severe sleep disturbances. CFCS generally carries a poor prognosis, underscoring the importance of disease awareness and early genetic testing. Abbreviations: RAS/MAPK=Ras/Mitogen-Activated Protein Kinase, RASopathies=RAS pathway diseases, RBD=RAS-binding domain, CRD=cysteine-rich domain, NS=noonan Syndrome, NSML= noonan syndrome with multiple lentigines, NF1=neurofibromatosis type I, CS=costello syndrome, LS=Legius syndrome, CSWS=continuous spike-and-wave during sleep.